(untitled) (Journal of Asian Development Studies, 2024)
Macroeconomic factors strongly influence the economy. It affects countries and businesses equally. The relationship between different macroeconomic factors is an area of widespread study for policymakers and economists. The ultimate purpose of this study is to assess the impact of macroeconomic factors on the economic growth.This research has taken GDP as a substitute variable for the development of the economy as well as endogenous (dependent) variable and FDI, inflation (INF), money supply (M2), public and private domestic investment (DINVEST), and foreign exchange reserve (FExR) as independent variables.Moreover, this study used time series secondary data starting from 2005-06 to 2022-23 for all econometric analysis. On the other side, we utilized the ADF (Augmented Dickey-Fuller) test to study the unit root (stationary property) of data, the Durbin Watson (DW) statistic technique to verify the autocorrelation of variables, the VIF test technique to examine the multicollinearity among independent variables and multiple linear regression to scrutinize the overall effect of macro-economic factors on growth of the economy.Study findings show that DINVEST and FDI positively affect thegrowthof the economy. i.e., if macroeconomic variables-DINVEST and FDI are increased by 1 unit, they increase economic growth by 2.96 units and 0.62 units, respectively. However, inflation, money supply, and foreign exchange reserves have a positive effect on economic growth, but it is statistically insignificant. The study implies that economists, researchers, academicians, and policymakers can use the findings of the study for future research anddecision-making regarding the effect of macroeconomic factors on economic growth